ANALISIS KOMODITI UNGGULAN DAN PERTUMBUHAN TANAMAN BUAH-BUAHAN DIKABUPATEN OGAN KOMERING ULU SELATAN (JASEP, 2019)
Subsector of fruit crops in South Ogan Komering Ulu Regency from 2012 to 2016 shows that fruit plants which are the leading commodities (Basis) are banana and duku. The non-superior ones are avocado, star fruit, durian, guava, guava, orange, orange, mango, jackfruit, mangosteen, papaya, rambutan, sapodilla, soursop, and breadfruit. And Shift share analysis shows that the production of fruits subsector in South Ogan Komering Ulu Regency has increased and positive number from 2012 until 2016. This shows good growth in fruits commodity in South Ogan Komering Ulu Regency.